Strength Behavior of Soil Cement Mixtures with and without Fly Ash for Can Tho Soft Soil - LE GIA LAM (Lowland Technology International, 2021)
This paper investigates strength of Can Tho soft soil mixed with cement and effect of the incorporation fly ash ratio on strength the mixed soil. The strength in terms of unconfined compressive strength of the mixtures was determined in the laboratory and used to evaluate strength of the soil cement mixing. The soil was blended with cement at proportion from 100 to 500 kg cement per cubic meter of soil to test the strength of the mixtures and propose a proper amount of cement for soil cement mixing. In addition, a number of tests was conducted for the soil mixed with different ratios from 10% to 50% of fly ash to cement to seek for suitable replacement of fly ash to cement and strength of soil mixed with cement and fly ash. As a result, the study shows that the strength of Can Tho soft soil improved with cement can reach above 1000 kPa when it mixed from at least 300 kg cement for a cubic meter of soil. When fly ash is incorporated, if the ratio of fly and cement is less than or equal 20%, the strength of the soil mixing is change not much and the replacement of cement by fly ash is suggested to limit to 20% to reach the strength nearly 1000 kPa. Additionally, the axial strain of cement-treated soil specimens with and without fly ash reduces very significantly to just under 2.5% compared to above 14% that of natural soil specimens.